Study on the Relationship between Macrovascular and Microvascular Hemodynamics - Figliuzzi, M. M.; Sestito, S.; Pacifico, D.; Parentela, L.; Rengo, Carlo (New Horizons in Medicine and Medical Research Vol. 8, 2022)
The aim of this study is to identify a possible link between macrovascular hemodynamic status and microvascular hemodynamic indices in patients with periodontal disease. The interactions between the macrovasculature and microvasculature have been little studied but understanding the interaction between these vessels may open new targets for treatment and management strategies. Seventeen adult patients are recruited on a voluntary basis at the Dentistry Department of the “Mater Domini” University of Catanzaro, with sampling that that determines the lipid profile, blood glucose, inflammatory mediators, blood plasma viscosity: anamnesis, blood pressure measurement, and detection of anthropometric parameters: eco-Doppler of the carotid arteries and brachial arteries with noninvasive measurements of hemodynamics and evaluation of inflammation and periodontal circulation with a noninvasive spectroscopic technique. The sites with high probing depth differ from the healthy ones, showing low oxygen saturation and a notable increase in tissue edema, but no correlation between macro- and microvascular values was found. Periodontal probing and spectroscopic examination revealed a correlation between low oxygen saturation levels and tissue edoema values as probing depth increased; however, no correlation between macrovascular hemodynamic status and microvascular hemodynamics indices was discovered, most likely due to the heterogeneity of the population studied, the small sample size, and the low number of data collected. It is possible that the two circulatory districts were not strongly connected in the gingival pathology, and due to the enlargement of the local gingivopathy, it was only the systematic inflammation which gave the verified worsening of the carotid hemodynamic situation in patients with periodontal disease.